1998
DOI: 10.1103/physrevlett.80.4843
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Radiation Instability in Hot Young Neutron Stars

Abstract: We show that gravitational radiation drives an instability in hot young rapidly rotating neutron stars. This instability occurs primarily in the l = 2 r-mode and will carry away most of the angular momentum of a rapidly rotating star by gravitational radiation. On the timescale needed to cool a young neutron star to about T = 10 9 K (about one year) this instability can reduce the rotation rate of a rapidly rotating star to about 0.076ΩK , where ΩK is the Keplerian angular velocity where mass shedding occurs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
771
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 424 publications
(803 citation statements)
references
References 10 publications
28
771
1
3
Order By: Relevance
“…Haskell 2015 for a recent review). The standard model of r-mode instability (suggested by Lindblom, Owen & Morsink 1998;Owen et al 1998, see also Gusakov, Chugunov & Kantor 2014a for discussion of recent microphysical updates) assumes a hadronic composition of the NS core and dissipation by shear and bulk viscosity. It stabilizes the NS in the grey region in Fig.…”
Section: Upper Limit For Surface Temperature Of Msp 47 Tuc Aa and Conmentioning
confidence: 99%
“…Haskell 2015 for a recent review). The standard model of r-mode instability (suggested by Lindblom, Owen & Morsink 1998;Owen et al 1998, see also Gusakov, Chugunov & Kantor 2014a for discussion of recent microphysical updates) assumes a hadronic composition of the NS core and dissipation by shear and bulk viscosity. It stabilizes the NS in the grey region in Fig.…”
Section: Upper Limit For Surface Temperature Of Msp 47 Tuc Aa and Conmentioning
confidence: 99%
“…15) Crustal heating has the following form: The other heating process is viscous heating, which originates because of the r-mode instability associated with the rapidly rotating NSs. 26,27) This process may affect the temperature evolution of NSs; 28) however, we do not include it in our study because the dimensionless amplitude of the r-mode is very uncertain, and the heating rates is unclear. 29) The accreted matter is assumed to have a uniform chemical composition with each mass fraction (X, Y, Z) = (0.73, 0.25, 0.02), where X, Y, and Z represent the mass fractions of hydrogen, helium, and heavy elements, respectively.…”
Section: /9mentioning
confidence: 99%
“…R-modes have been of particular interest to GW studies (e.g., Lindblom, Owen, & Morsink 1998;Andersson, Kokkotas, & Schutz 1999;) because they are unstable to GW emission: gravitational radiation tends to increase the amplitude of the mode. Lindblom, Owen, & Morsink (1998) first mapped out the range of stellar spin and temperature for which the viscosity was unlikely to damp away this runaway growth, and concluded that many hot, young neutron stars were likely to be important sources of GWs. Current thinking is that the rmodes of young hot neutron stars are actually unlikely to be important sources of GWs.…”
Section: R-modesmentioning
confidence: 99%
“…Understanding the physical nature of noise in GW detectors is an active field of current research; see Levin (1998), Liu & Thorne (2000, Santamore & Levin (2001), Buonanno & Chen (2001a,b), Hughes & Thorne (1998), Creighton (2000), and references therein for a glimpse of recent work. In all cases, the fundamental fact to keep in mind is that a GW acts coherently, whereas noise acts incoherently, and thus can be beaten down provided one is able to average away the incoherent noise sources.…”
Section: Gws and Detectors: Overviewmentioning
confidence: 99%
See 1 more Smart Citation